Cultural religiosity moderates the relationship between being in love and subjective well-being - Olechowski, M.; Górski, M. R.; Joshanloo, M.; Hussain, M. A.; Wasiel, A.; Yeung, V. W. L.; Bond, M. H.; Haas, B. W.; Guemaz, F.; Boussena, M.; Sánchez-Rodríguez, Á.; Iter, N.; et al. (International Journal of Intercultural Relations, 2025)
Previous research indicates that the significance of love varies considerably across cultures. In the present study, we introduce an often-overlooked cultural factor – religiosity – to explore its influence on the relationship between being in love and five dimensions of subjective well-being. We conducted two cross-cultural studies with 31,608 participants from 117 samples across 83 societies. Our findings reveal that, in more religious cultures, being in love is a weaker predictor of well-being compared to more secular cultures in four out of six models. These findings indicate that national context influences the relative importance of various emotions and experiences for well-being, underscoring the need to account for cultural context in research on love.